2022
DOI: 10.3389/fmicb.2021.800190
|View full text |Cite
|
Sign up to set email alerts
|

The Phylosymbiosis Pattern Between the Fig Wasps of the Same Genus and Their Associated Microbiota

Abstract: Microbial communities can be critical for many metazoans, which can lead to the observation of phylosymbiosis with phylogenetically related species sharing similar microbial communities. Most of the previous studies on phylosymbiosis were conducted across the host families or genera. However, it is unclear whether the phylosymbiosis signal is still prevalent at lower taxonomic levels. In this study, 54 individuals from six species of the fig wasp genus Ceratosolen (Hymenoptera: Agaonidae) collected from nine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Within the genus Ototyphlonemertes , species identity explained about 40% of the differences in microbiome composition between individuals and there was a significant correlation between phylogenetic distances of the hosts and differences in community composition of the associated microbial communities, regardless of geographical distances. Our results align with numerous prior studies on phylosymbiosis across diverse animal taxa, as the observed pattern of phylosymbiosis between nemertean species and their associated microbiome provides evidence for the existence of a complex interplay between host identity and microbial diversity (Li et al, 2022;Tinker & Ottesen, 2020). Moreover, these results are consistent with previous investigations focusing on nemertean taxa associated with toxicity, which also demonstrated a strong association between nemertean species and their associated microbiome (Melnikova & Magarlamov, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Within the genus Ototyphlonemertes , species identity explained about 40% of the differences in microbiome composition between individuals and there was a significant correlation between phylogenetic distances of the hosts and differences in community composition of the associated microbial communities, regardless of geographical distances. Our results align with numerous prior studies on phylosymbiosis across diverse animal taxa, as the observed pattern of phylosymbiosis between nemertean species and their associated microbiome provides evidence for the existence of a complex interplay between host identity and microbial diversity (Li et al, 2022;Tinker & Ottesen, 2020). Moreover, these results are consistent with previous investigations focusing on nemertean taxa associated with toxicity, which also demonstrated a strong association between nemertean species and their associated microbiome (Melnikova & Magarlamov, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Most studies investigating patterns of phylosymbiosis have predominantly focused on only a small fraction of animals such as mammals and other vertebrates (Brown et al, 2023;Ley et al, 2008;Moeller et al, 2017;Sadeghi et al, 2022), arthropods, particularly insects (Dunaj et al, 2020;Li et al, 2022;Tinker & Ottesen, 2020), or corals and sponges (Moitinho-Silva et al, 2017;Pushpakumara et al, 2023;Röthig et al, 2016;Sweet & Bulling, 2017;Thomas et al, 2016). Other organisms residing in various ecosystems and distinguished by a range of life histories have received relatively less attention in comparison.…”
Section: Introductionmentioning
confidence: 99%
“…In fungus-growing ants, cultivated fungi serve as the sole nutritional source for the larvae of attine ants [88]. Phylosymbiosis has been revealed in several Hymenoptera groups, i.e., fig wasps (Ceratosolen), parasitoid wasps (Nasonia), turtle ants (Cephalotes), and Formica ants [10,41,42,44]. Under controlled rearing conditions, the bacterial communities of parasitoid wasps of Nasonia mirror the host phylogeny at different developmental stages [9].…”
Section: Hymenopteramentioning
confidence: 99%